Pengaruh Perubahan Cara Latihan Terhadap Mental Dan Stamina Dalam Menjaga Kekuatan Fisik Dan Tehnik Para Olahragawan Di Masa Pandemi Covid-19 - Bobby Kurnia Putrawan; Jerry Sucipto Thauwrisan (Ilmu Olahraga, 2023)
For an athlete, physical and technical exercise is something that must be done every day in order to be able to increase the ability and strength of the athlete. Unfortunately, unexpectedly, the COVID-19 virus outbreak that hit especially in Indonesia in 2020 made all activities have to be done at home. Studying, working, worshiping, even practicing sports are required from home. With this changing situation, the Indonesian National Sports Committee (abbreviated as KONI) as the only organization that is responsible for managing, fostering, developing & coordinating the entire implementation of the sporting achievements of each member in Indonesia must find a way out so that all athletes immediately adapt and are able to run exercise program properly while maintaining their physical fitness in the midst of the current Corona virus (Covid-19) pandemic. With the change in the way of training online, KONI hopes that it can run well while seeing how it impacts the mentality of each athlete. The purpose of this study is to see how the exercise mechanism of the athletes, even in a completely different way, still meets the targets that have been set by each coach.